Leadership Influence On Process Improvement In The Precast Concrete Industry - Laurence Alberto, Charles Alberto (2009)
Leadership influence and involvement are crucial in any process improvement initiatives. Not many leaders understand the need to constantly support and walk the talk in process improvement initiatives. Their only concern is how to make more money for the organization not realizing that their actions and decisions have an impact on process improvement initiatives in the organization. As a result, process improvement initiatives are not sustainable in many organizations.